2004
DOI: 10.1262/jrd.50.685
|View full text |Cite
|
Sign up to set email alerts
|

High Survival Rate of Bovine Oocytes Matured In Vitro Following Vitrification

Abstract: Abstract. Improving pregnancy rates associated with the use of cryopreserved human oocytes would be an important advance in human assisted reproductive technology (ART). Vitrification allows glasslike solidification of a solution without ice crystal formation in the living cells. We have attempted to improve the survival rates of oocytes by a vitrification technique using bovine models. In vitro matured oocytes with or without cumulus cells were vitrified with either 15.0% (v/v) ethylene glycol (EG) + 15% (v/v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 76 publications
4
100
0
5
Order By: Relevance
“…Therefore, when embryos were exposed to the entire cryoprotectant solutions, survival rates were similar for solutions composed with EG and significant lower for PROH-DF cryoprotectant association. These results confirm the previously described by other authors (EMILIANI et al, 2000;CHIAN et al, 2004), Where EG presence in cryoprotectant solutions showed lower toxicity effects on in vitro viability.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, when embryos were exposed to the entire cryoprotectant solutions, survival rates were similar for solutions composed with EG and significant lower for PROH-DF cryoprotectant association. These results confirm the previously described by other authors (EMILIANI et al, 2000;CHIAN et al, 2004), Where EG presence in cryoprotectant solutions showed lower toxicity effects on in vitro viability.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, the potential protective role of the cumulus during the vitrification of MII oocytes remains controversial, not least because some studies still record better results for cumulus-enclosed than denuded human vitrified oocytes (e.g. Kuwayama et al 2005); there may also be between-species differences since there are reports of reduced oocyte viability and developmental competence in cattle oocytes vitrified with an intact cumulus (Chian et al 2004), no effect of cumulus presence during vitrification of sheep oocytes ) and either a protective effect of the cumulus ( Varga et al 2006) or an effect of cumulus presence on the optimal time for exposing MII oocytes to CPA in pigs ( Fujihira et al 2005). Since there are considerable apparent between-species and study differences, it was appropriate to examine the effect of vitrifying MII equine oocytes with or without their cumulus investment on post-warming meiotic spindle quality.…”
Section: Discussionmentioning
confidence: 99%
“…A similar protective effect of the cumulus during the vitrification of MII equine oocytes is inferred by the observations that horse oocytes vitrified at the MII stage within their cumulus investments were able to yield viable pregnancies (Maclellan et al 2002), whereas vitrification of denuded MII horse oocytes led to a high incidence of spindle abnormalities (O65%) and very poor developmental competence following intracytoplasmic sperm injection ( Tharasanit et al 2006b). On the other hand, current protocols for cryopreserving MII human oocytes almost universally involve prior denudation, since more recent studies have concluded that totally removing the cumulus prior to controlled-rate freezing does not reduce the viability of human oocytes ( Fabbri et al 2001), and may even improve the developmental competence of bovine oocytes vitrified using the cryotop technique (Chian et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Embryos may pass rapidly through the dangerous zone (temperature range from +20 to -20 o C), which decreases the risk of chilling injury. This method has been applied to various species for embryo cryopreservation, including the cow (Chian et al, 2004), rabbit (Hochi et al, 2004), buffalo (Muenthaisong et al, 2007), pig (Du et al, 2007) and human (Antinori et al, 2007).…”
Section: Cryotop (Also Called Minimum-volume Cooling)mentioning
confidence: 99%